Dante’s Inferno, LGBT-Q, and Christianity: A Closer Reading on Medieval Christian Perspective Regarding Homosexuality - Abdullah Muslich Rizal Maulana; Nuur Aini Hajrah Arifin; Muhammad Nurrosyid Huda Setiawan; Farhah Farhah (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2024)
This paper is a qualitative theological research discussing Dante Alighieri’s (d. 1321) account of LGBT-Q (Lesbian, Gay, Bisexual, Transgender, Queer) based on his major work, Inferno, with a particular reference to Medieval Christian tradition. Accordingly, this paper used content analysis to apprehend major literature on Dante and LGBT-Q. This paper concluded that the term Sodom and Gomorrah, the cities demolished due to homosexual violation, is apparent in his work. Furthermore, as several Biblical texts also suited the concrete image of those cities, Dante’s Inferno also presented Medieval Christian position concerning homosexuality, which is condemn homosexuality as lust against the role of nature, so it is equated with committing violence against God.